(untitled) - Watson, Lyall (London, 1974)
The book is at its best when it examines the fuzzy spots around the borders of science and he does a solid clear-headed assessment of some of the shortcomings of the scientific-materialist metaphysics of many scientists today.
Keywords: Thuyết huyền bí,Occultism